Total Cerebral Small Vessel Disease MRI Score Is Associated with Cognitive Decline in Executive Function in Patients with Hypertension - Uiterwijk, Renske; van Oostenbrugge, Robert J.; Huijts, Marjolein; De Leeuw, Peter W.; Kroon, Abraham A.; Staals, Julie (Frontiers in Aging Neuroscience, 2016)
Objectives: Hypertension is a major risk factor for white matter hyperintensities, lacunes, cerebral microbleeds and perivascular spaces, which are MRI markers of cerebral small vessel disease (SVD). Studies have shown associations between these individual MRI markers and cognitive functioning and decline. Recently, a “total SVD score” was proposed in which the different MRI markers were combined into one measure of SVD, to capture total SVD-related brain damage. We investigated if this SVD score was associated with cognitive decline over 4 years in patients with hypertension. Methods: In this longitudinal cohort study, 130 hypertensive patients (91 patients with uncomplicated hypertension and 39 hypertensive patients with a lacunar stroke) were included. They underwent a neuropsychological assessment at baseline and after 4 years. The presence of white matter hyperintensities, lacunes, cerebral microbleeds, and perivascular spaces were rated on baseline MRI. Presence of each individual marker was added to calculate the total SVD score (range 0-4) in each patient. Results: Uncorrected linear regression analyses showed associations between SVD score and decline in overall cognition (p=0.017), executive functioning (p<0.001) and information processing speed (p=0.037), but not with memory (p=0.911). The association between SVD score and decline in overall cognition and executive function remained significant after adjustment for age, sex, education, anxiety and depression score, potential vascular risk factors, patient group and baseline cognitive performance. Conclusions: Our study shows that a total SVD score can predict cognitive decline, specifically in executive function, over 4 years in hypertensive patients. This emphasizes the importance of considering total brain damage due to SVD.